Game theory as a tool for making optimal business decisions in foreign economic activity of enterprises - Havrys, Olha; Sun, Changan; Kuchina, Svetlana; Gavrys, Mykola (Національний технічний університет "Харківський політехнічний інститут", 2024)
The article is devoted to the study of the effectiveness of game theory in making business decisions regarding foreign economic activity by enterprises in conditions of uncertainty. The sources of information on this issue were analyzed and it was found that further development of the application of game theory in the foreign economic activity of enterprises is necessary. It has been established that the ambiguity of economic development trends, which has been especially evident in recent years in Ukraine and the world, and the instability of the market regulation mechanism encourage enterprises to look for new ways to overcome uncertainty in their activities. When solving economic problems, conflict situations often arise, which are caused by the conflicting interests of various structures. The mathematical apparatus for solving this type of problem is game theory, which is the theory of building mathematical models of optimal decision-making in conflict conditions. Game theory is a theoretical direction in science, a set of methods of mathematical analysis and assessment of the rules of behavior of participants in a conflict situation, which involves the interaction of two or more participants (players) in order for each of them to achieve their goals. The advantages of game theory are analyzed, in particular, the possibility of formalizing the process of considering typical scenarios of decision-making by the parties to the conflict and choosing the procedure for coordinating interests that will be optimal for all its participants. The main concepts, principles and classifications of game theory are presented, the foundations for understanding the use of game theory in economics are laid. Analyzing the usefulness of game theory in market competition, development of enterprise development strategy, investment activities and other areas, the possibility of wide application and effectiveness of game theory in decision-making regarding foreign economic activities of enterprises is shown.

Стаття присвячена дослідженню ефективності теорії ігор у прийнятті господарських рішень щодо зовнішньоекономічної діяльності підприємствами в умовах невизначеності. Проаналізовано джерела інформації з даного питання і виявлено, що не обхідні подальші розробки застосування теорії ігор в зовнішньоекономічній діяльності підприємств. Встановлено, що неоднозначність тенденцій економічного розвитку, яка особливо проявляється останніми роками в Україні та світі, та нестабільність механізму ринкового регулювання спонукають підприємства шукати нові шляхи подолання невизначеності у своїй діяльності. При вирішенні економічних проблем часто виникають конфліктні ситуації, які викликані суперечливими інтересами різних структур. Математичним апаратом розв’язування такого типу задач є теорія ігор, яка є теорією побудови математичних моделей прийняття оптимальних рішень в умовах конфлікту. Теорія ігор — теоретичний напрям у науці, сукупність методів математичного аналізу та оцінки правил поведінки учасників конфліктної ситуації, що передбачає взаємодію двох або більше учасників (гравців) з метою досягнення кожним із них їхні цілі. Проаналізовано переваги теорії ігор, зокрема можливість формалізації процесу розгляду типових сценаріїв прийняття рішень сторонами конфлікту та вибору процедури узгодження інтересів, яка буде оптимальною для всіх його учасників. Викладено основні поняття, принципи та класифікації теорії ігор, закладено основи розуміння використання теорії ігор в економіці. Аналізуючи корисність теорії ігор у ринковій конкуренції, розробці стратегії розвитку підприємства, інвестиційній діяльності та інших сферах, показано можливість широкого застосування та ефективність теорії ігор у прийнятті рішень щодо зовнішньоекономічної діяльності підприємств.
Теорія ігр як інструмент прийняття оптимальних бізнес-рішень у зовнішньоекономічній діяльності підприємств
Keywords: game theory; foreign economic activity; business decisions; uncertainty; conflicting interests; decision-making criteria; теорія ігор; зовнішньоекономічна діяльність; бізнес-рішення; бізнес-рішення; конфлікт інтересів; критерії прийняття рішень